Studies on Biodiesel Production Technology from Jatropha curcas and its Performance in a CI Engine - Sahoo, P K; Naik, S N; Das, L M (Journal of Agricultural Engineering, 2005)
The importance of diesel fuel in Indian context is very different from that in the developed countries. Diesel is being used in mechanized agricultural, public transportation sector and also for several other applications. In the wake of the present fuel crisis, it has become essential to identify some renewable and environmentally compatible substitutes to diesel fuel. In the present investigation the high viscosity of the Jatropha curcas oil which has been considered as a potential alternative fuel for the diesel engine was decreased by transesterification (methanolysis) and blending the methyl ester with diesel. Three test fuels of neat disel; blends of 20% volume (B20) of proportions of jatropha oil methyl ester (JOME) with diesel; and neat JOME (B100) were prepared, analyzed and compared with diesel fuel. The performance and exhaust emission of the engine using blend of 20% JOME With diesel and neat JOME was evaluated in a single cylinder C.I. engine and compared with the performance obtained with diesel. Significant improvement in engine performance was observed compared to biodiesel alone. The specific fuel consumption and the exhaust gas temperature were reduced due to decrease in viscosity of the biodiesel. Acceptable thermal efficiencies of the engine were obtained with neat JOME (100% volume of JOME). Exhaust emission behavior was environment friendly. From the properties and engine test results it has been established that 100% of jatropha oil methyl ester can be substituted for diesel without any engine modification.